Factors influencing students being deceived in pyramid scheme: Study on universities in Malaysia - Hawa Nur Sai'dah, Mustaffa (2021)
Since its heyday in the 1920s, the pyramid scheme industry has become a difficult battleground. Since its inception, the pyramid scheme has evolved into a variety of shapes and styles. Malaysia is also not immune to pyramid scheme interference. And participation in this pyramid system disregards age and category. This research focuses on the students being deceived in pyramid schemes. It is intended to measure the factor that might affect the involvement of students being duped in pyramid schemes, including the ambitious, desire to try, surrounding society, family background, and deceived by advertising. This study examines the relationships between the ambitious with being duped in pyramid schemes. This study employed a quantitative method where a questionnaire is used as a method in the collection of the data. The hypothesized relationships are tested using survey responses from 119 respondents, consisting of university students in Malaysia. The finding of the study revealed that two determinants had a positive relationship being deceived in pyramid schemes among the students: family background and surrounding society. This study’s findings are able for universities and industries can revise their policies to discern the extent of student involvement in the pyramid scheme businesses and take the initiative to help students who fall into this scheme. Further study might examine the operations of con artists to interdict them. Further research might also consider ethical behaviour in a technology-mediated channel where the opposing party is not another human but a computer.